Can simple clinical tests predict walking ability after prosthetic rehabilitation? - Sansam, K; O’Connor, R; Neumann, V; Bhakta, B (Journal of rehabilitation medicine, 2012)
To investigate whether simple clinical measures can predict walking ability after lower limb prosthetic rehabilitation. Prospective observational study. Ninety five adults who were assessed as suitable for lower limb prosthetic rehabilitation by the multidisciplinary team. Information regarding baseline clinical factors (amputation details, comorbidities, physical ability, mood and cognitive ability) was collected prior to provision of the prosthesis. Backward step linear regression was used to identify factors predictive of performance on the Timed Up and Go test following rehabilitation. Seventy one participants were able to complete this walking test and were included in the final analysis. The backward step regression model had an adjusted R2 of 0.588 and comprised 6 factors: age (p = 0.002), gender (p = 0.027), level of amputation (p = 0.000), presence of contracture (p = 0.088), ability to stand on one leg (p = 0.062) and Trail Making Tests A + B (p = 0.047), a test of cognitive flexibility. Cause of amputation (dysvascular or non-dysvascular) was not an independent predictor of walking outcome. These results indicate that simple clinical assessments completed prior to prosthetic provision can be used to predict mobility outcome. These findings need to be validated in a larger population across other amputee rehabilitation services and if confirmed could easily be incorporated into routine clinical practice.